The expansion of isms, 1820–1917: Data-driven analysis of political language in digitized newspaper collections - Marjanen, Jani; Kurunmäki, Jussi; Pivovarova, Lidia; Zosa, Elaine (Journal of data mining and digital humanities, 2020)
Words with the suffix-ism are reductionist terms that help us navigate complex social issues by using a simple one-word label for them. On the one hand they are often associated with political ideologies, but on the other they are present in many other domains of language, especially culture, science, and religion. This has not always been the case. This paper studies isms in a historical record of digitized newspapers from 1820 to 1917 published in Finland to find out how the language of isms developed historically. We use diachronic word embeddings and affinity propagation clustering to trace how new isms entered the lexicon and how they relate to one another over time. We are able to show how they became more common and entered more and more domains. Still, the uses of isms as traditions for political action and thinking stand out in our analysis.